(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objective: The purpose of this research is to identify problems that arise while producing death certificates in the tertiary care hospital setting and to propose ways to fix them in order to avoid any medicolegal complications later. Methods: This retrospective observational study aimed to sample and audit the mortality status & quality of death certification in the medical intensive-care unit (ICU) of a tertiary care, thirdlargest hospital in Karachi, the Abbasi Shaheed hospital, for the period January 2018 to December 2018. Using a predetermined standard form, we gathered information from death certificates including demographics, administration, comorbidities, and causes of death. Their medical records were used to confirm the accuracy of this data. The death certificates were graded on a scale from zero to five, with a zero being assigned if no mistakes were found to a five if the wrong cause of death was listed or listed in the wrong order. Results: Over the course of the study's 12-month duration, 283 death certificates were examined. Of the total 283, 140 were women and 143 were men. About a quarter of all certificates of death include no inaccuracy of any kind. Grade III errors (co-morbidities list was not stated) made up 64% of all the errors found in the audited certificates, while Grade IV errors (18%) stood second. At least one mistake was found in 138 certificates. Sixty-nine of the death certificates include at least two mistakes. Conclusion: Death certificates prepared at a tertiary care hospital were found to include an extremely high mistake rate. Such mistakes could lead to medicolegal complications. Appropriate intervention(s) are urgently required to address this critical problem.